Impacto da recompra de ações no valor de mercado da ação: uma análise no mercado brasileiro no período de 1998 a 2008 - Abreu, Regilane Lacerda (2010)
This study aims at testing the semi-strong form of market efficiency, which presumes that the prices should reflect all publicly available information, and at verifying the effects of the anomaly of announcements determined by the behavioural finances, specifically, the announcement of share repurchase by the open companies in Brazil, analyzing its effects in the share market value of those companies listed on Bovespa through the application of event study whose data were obtained from both the Economatica database and the São Paulo Stock Exchange (Bovespa). The study concentrates in the verification of abnormal return on the announcement dates of share repurchase announced by the companies listed on Bovespa from 1998 to 2008. An event study methodology was applied using the logarithmic approach of continuous capitalization to estimate the returns of shares and the return of Ibovespa. Regarding that event, the return of shares of those companies in the Brazilian Stock Market was investigated in a period shorter than or longer than 20 days around the event, comparing it with the return of portfolio market represented by Ibovespa. It was possible to determine the presence of abnormal returns in the share prices statistically superior than the returns of Ibovespa, indicating that probably occurred a stronger valorization of the companies that announced share repurchase in the years studied according to the methodology adopted for this study. The t-Student test was applied for testing the statistical significance of the results, leading to the rejection of a null hypothesis that the abnormal variation in the return of the shares around the date of the repurchase announcement is equal to zero. The regression analysis certifies that the variation in the Ibovespa s portfolio market is not enough to explain the abnormal returns of the shares analysed. Those results lead to the rejection of the hypothesis that the semi-strong form of market was efficient in the period covered by this research since the presence of abnormal returns indicate that the market was not efficient in its semi-strong form after the share repurchase announcements in that period